Pengaruh Kompensasi Terhadap Kinerja Pegawai Dengan Motivasi Kerja Sebagai Variabel Intervening - Guntoro; Djunaedi; Utami, Sasi (Fakultas Ekonomi Universitas KH. A. Wahab Hasbullah Tambakberas Jombang, 2024)
This study aims to determine the effect of compensation on employee performance through work motivation at the cooperative and micro-enterprise services in the Nganjuk district. This type of research uses descriptive quantitative with a survey approach where the questionnaire will be distributed to all research respondents. The population in this study is all employees of the Nganjuk district cooperative and micro-enterprise services, totaling 55 people. In determining the sample, saturated sampling was used, where the entire population is used as a respondent, considering the population is less than 100. Path analysis was used to test the results of the respondents' data to measure the effect of the dependent variable on the independent variable. The test results show that direct compensation significantly affects the performance of employees of the Nganjuk Regency Cooperative and Micro Business Office. Indirectly, motivation can mediate the effect of compensation on the performance of the Nganjuk Regency Cooperative and Micro Business Office employees.